La responsabilidad social empresarial en las microempresas del sector de la construcción en Colombia (2023)
Corporate Social Responsibility is a term that encompasses the set of social, economic and environmental actions, to favorably improve the conditions and/or relationships of the organization's stakeholders. Currently, it is a concept adopted mostly by large companies, which through programs seek to improve their image in society and positively influence the conditions of their collaborators. This document aims to establish a CSR policy guide for microenterprises in the construction sector, based on the actions conceived by the large companies in the sector and the analysis of a group of microenterprises that adopt and/or want to implement programs to strengthen their work team.